Rekonstruksi Mekanisme Hukum dalam Pencabutan Izin Usaha Pertambangan Berdasarkan Asas Kemanfaatan Hukum - Situmeang, Ojak; Redi, Ahmad (Pascasarjana UDA, 2023)
The application of the principle of legal benefit in the revocation of Mining Business Licenses (IUP) in Indonesia plays an important role in achieving the goals of social welfare, environmental sustainability, and economic sustainability. This principle prioritizes the use of law for the benefit of society and the state, with an emphasis on the balance between natural resource management and environmental protection. This study discusses the application of the principle of legal benefit in the process of revoking IUP, the factors that influence the decision, and the obstacles faced in its implementation. Improvements in the legal system, supervision, and transparency are needed to overcome existing challenges, as well as improvements to laws and regulations to support economic sustainability and environmental protection. Improving the application of the principle of legal benefit will ensure that the mining sector can operate responsibly and sustainably.